Considerations on the prevention of infanticide - Avendaño, L. (1919)
I think it is mandatory for the master of Legal Medicine, addressing the inaugural lecture in the course of any of the countless topics that relate to matters of public medicine. It is necessary that students will begin the study of this important discipline of medical science, realize, from the outset, the dominant role played by the Forensic Medicine in the stock of human knowledge. Science, facts and observation, using the teachings of all others, whether principal or accessory; contribution that puts its multiple applications and incessant few discoveries has made the portentous human intellect; that through its exercise and its intervention in the administration of justice, provides the most effective means of prudential life, honor and interests of humanity 18; and widening every day more and more its vast scope, realization can be considered without us being branded as exaggerated as the most useful and beneficial for social organization.